Investigation of surface integrity induced on AZ31C magnesium alloy turned under cryogenic and dry conditions - Danish, M. (Elsevier B.V., 2019)
Magnesium alloys have been found as a very attractive candidate for wide variety of applications such as automobiles, aerospace and biomedical implants due to its biocompatibility and high strength to weight ratio. However, ignition risk during machining of magnesium and high corrosion rate has hindered their applications. This paper investigates the influence of cryogenic machining of AZ31C magnesium alloy on several critical surface integrity parameters (surface roughness, crystallographic planes, microstructures and microhardness). For this, cryogenic as well as dry turning experiments were performed. Significant improvement in the surface finish was found in the cryogenic turned samples. X-ray diffraction patterns confirmed that the intensity of basal plane (0002) was much higher for cryogenically turned samples. Grain refinement layer was observed on the turned samples and it was found to be thinner for turned samples. Cryogenic machining was also able to increase the microhardness up to 98.6 HV from 53.7 HV. To sum up, cryogenic machining has induced beneficial surface integrity and quality that not only helps in improving the corrosion resistance but also enhances its sustainability and reduces ignition risk. Â© 2019 The Authors. Published by Elsevier B.V.